EXCLI Journal; 21:Doc772; ISSN 1611-2156 2022
DOI: 10.17179/excli2022-4764
|View full text |Cite
|
Sign up to set email alerts
|

Plasma lncRNA profiling identified BC200 and NEAT1 lncRNAs as potential blood-based biomarkers for late-onset Alzheimer’s disease

Abstract: Long non-coding RNAs (lncRNA) play critical roles in pathogenesis of neurodegenerative diseases. Human plasma carries lncRNAs that are stable in the blood, and their disease-specific profile have made them valuable biomarkers for some diseases. This study reports screening of the plasma levels of 90 lncRNAs in patients with Alzheimer disease (AD) to find out plasma-based AD biomarkers. Total RNA was isolated from plasma samples of 50 AD and 50 matched healthy controls. The plasma samples of 10 advanced AD pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 45 publications
0
18
0
Order By: Relevance
“…Among seven lncRNAs, three lncRNAs were reported to be upregulated (RNA BACE-AS1, RNA NEAT1, RNA GAS5) [ 22 , 30 , 31 , 34 ]. BACE1-AS lncRNA was confirmed in more than one study as significantly upregulated in plasma samples [ 22 , 31 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among seven lncRNAs, three lncRNAs were reported to be upregulated (RNA BACE-AS1, RNA NEAT1, RNA GAS5) [ 22 , 30 , 31 , 34 ]. BACE1-AS lncRNA was confirmed in more than one study as significantly upregulated in plasma samples [ 22 , 31 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, RNA 51A and RNA BC200 were reported to have variable expression patterns. Deng et al and Khodayi et al reported, respectively, significant upregulation of RNA 51A and BC200 in the plasma of AD patients compared to healthy controls [ 32 , 34 ]. However, Feng et al [ 30 ] and Wang et al [ 31 ] did not find any significant difference between AD and healthy controls regarding 51A and BC200 lncRNA.…”
Section: Resultsmentioning
confidence: 99%
“…They also showed that BC200 might be a potent positive regulator of BACE1, and could reduce apoptosis and increase viability of the AD cells (Li et al, 2018[ 74 ]). Remarkably, BC200 plasma levels have recently been reported to be higher in AD patients, implying its potential as a blood-based biomarker for early diagnosis of AD (Khodayi et al, 2022[ 64 ]).…”
Section: Lncrnas In Synaptic and Neuron Plasticitymentioning
confidence: 99%
“…The mechanism of action of BC200 involves the PI3K/AKT axis found both in cancer cells [65] and in an AD model, associated with inflammation [66]. Interestingly, plasma BC200 has been found to be able to discriminate healthy controls from preclinical cases [67].…”
Section: Brain Cytoplasmic 200 (Bc200mentioning
confidence: 99%